Macrozoobenthos as Ecological Indicators: Evaluation of Water Quality in the Lematang River - Amin, Rejo; Siti Aulia Nurainah; Laila , Hanum (BIOVALENTIA: Biological Research Journal, 2025)
Rivers, as part of the hydrological cycle, have long been an important element of human civilization. The Lematang River, which flows through South Sumatra, plays a key role in supporting local livelihoods by providing resources for activities such as sand and stone mining, fishing, and other economic activities. Water quality assessment can be effectively conducted using macrozoobenthos as biological indicators. This study aimed to assess the water quality of the Lematang River in Lahat Regency using the Family Biotic Index (FBI) and a purposive sampling approach. The FBI scores recorded at Stations I, II, and III ranged from 3.6 to 4.2, indicating slight variation between locations. Based on FBI standards, these results classify the water quality of the river in the study area as ranging from Good to Very Good.